Simulation-Driven Optimization of Thermochemical Energy Storage in SrCl2-Based System for Integration with Solar Energy Technology - Suratsavadee K. Korkua; Uthen Thubsuang; Siraporn Sakphrom; Santanu Kumar Dash; Chalearm Tesanu; Kamon Thinsurat (Inventions)
This study presents a simulation-driven optimization of thermochemical energy storage using SrCl2-based systems for integration with solar energy technologies. Thermochemical sorption systems offer promising potential for enhancing solar energy-storage efficiency by capturing both thermal and electrical energy. However, optimizing sorption processes remains crucial for maximizing energy storage capacity. This work utilized advanced simulation tools to analyze the heat and mass transfer dynamics within SrCl2-EG composites and evaluate system performance under varying compression ratios (CR), reactant temperatures, and heat transfer fluid (HTF) flow rates. The results demonstrate that adjusting CR enhances the overall system efficiency. CR = 4 yields the highest desorption rate of 93.8%, while reducing the required HTF mass flow by nearly tenfold compared to lower CR values. Higher CR contributes to a reduction in sensible heat loss, allowing a greater percentage of thermal energy to be captured. Simulations also show that optimized SrCl2-based systems can integrate effectively with solar energy conversion technologies, making them highly suitable for both energy storage and cooling applications. This research underscores the role of thermochemical energy storage systems in providing more sustainable and efficient solar energy solutions. By reducing energy losses and improving the reliability of the energy storage process, SrCl2-based systems offer significant advantages for renewable energy integration.